Emergence of a tet(M) Variant Conferring Resistance to Tigecycline in Streptococcus suis - Yu, Rui; Zhang, Yue; Xu, Yindi; Schwarz, Stefan; Li, Xin-Sheng; Shang, Yan-Hong; Du, Xiang-Dang (Frontiers in Veterinary Science, 2021)
The aim of this study was to gain insight into the resistance determinants conferring resisitance to tigecycline in Streptococcus (S.) suis and to investigate the genetic elements involved in their horizontal transfer. A total of 31 tetracycline-resistant S. suis isolates were screened for tigecycline resistance by broth microdilution. S. suis isolate SC128 was subjected to whole genome sequencing with particular reference to resistance determinants involved in tigecycline resistance. Transferability of genomic island (GI) GISsuSC128 was investigated by transformation. The roles of tet(L) or tet(M) in contributing to tigecycline resistance in S. suis was confirmed by transformation using different tet(L)- or tet(M)-carrying constructs. Only S. suis SC128 showed a tigecycline resistance phenotype. A tet(L)-tet(M) and catA8 co-carrying GISsuSC128 was identified in this isolate. After transfer of the novel GI into a susceptible recipient, this recipient showed the same tigecycline resistance phenotype. Further transfer experiments with specific tet(L)- or tet(M)-carrying constructs confirmed that only tet(M), but not tet(L), contributes to resistance to tigecycline. Protein sequence analysis identified a Tet(M) variant, which is responsible for tigecycline resistance in S. suis SC128. It displayed 94.8% amino acid identity with the reference Tet(M) of Enterococcus faecium DO plasmid 1. To the best of our knowledge, this is the first time that a tet(M) variant conferring resistance to tigecycline was identified in S. suis. Its location on a GI will accelerate its transmission among the S. suis population.